Ethylene response factors as potential regulators of cell wall formation in celery (Apium graveolens L.) collenchyma: phylogeny and gene expression analysis. - Syrchina, Natalya; Mikshina, Polina; Mokshina, Natalia (Protoplasma, 2025)
Collenchyma is a mechanical tissue characterized by cells that can elongate despite having thickened cell walls. This ability to elongate, along with the biochemical composition of the collenchyma cell wall, allows it to be referred to as the primary cell wall (PCW). However, the regulation of PCW biosynthesis, even at the master switch level, remains a stumbling block for cell wall biologists. While only a few members of the IIId and IIIe phylogenetic subgroups of ethylene response factors (ERFs) have been identified as regulators of PCW formation, an analysis of the differential expression of AgrERFs was conducted to uncover potential regulators involved in collenchyma cell wall formation. Additionally, we performed a phylogenetic analysis of celery AgrERFs for comprehensive revision and annotation. A separate effort was dedicated to identifying reference genes for celery, utilizing the quantitative real-time PCR technique. The most stably expressed genes, TIP41 and CACTIN, were selected as reference genes for this species. Transcriptome profiling of celery petiole tissues revealed a group of AgrERFs that are highly and specifically expressed in collenchyma during petiole growth. Among these, AgrERF002b, AgrERF041b, and AgrERF079 had the highest correlation coefficients of coexpression with genes encoding cell wall-related proteins, including cellulose synthases involved in PCW biosynthesis (AgrCESA1, 3, and 6). This suggests a potential role of these transcription factors in regulating PCW biosynthesis. Furthermore, AgrERF039, a member of the IIId group, along with several other AgrERFs, was coexpressed with genes encoding secondary cell wall-related cellulose synthases (AgrCESA4, 7, and 8).